DMF-T index of 12-15 years old children - Alfira, Sarah Vania; Aripin, Dudi; Setiawan, Asty Samiaty (Universitas Padjadjaran, 2010)
Introduction: Dental caries z a disease which is often found at every social strata of Indonesian people at men or woman and children or adult. According to the Survey of Health Family in the year of 2001, case numbers of dental caries in Indonesia was 76,2% at age group 12 years. This research is aim to identifying the DMF-T index of 12-15 years old children in 2nd Junior High School (SMP Negeri 2) PTPN VIII in Pangalengan. Methods: The descriptive method was applied for data analysis. The structured interview technique was applied for collecting the data needed in this study. The respondents included in the study were 122 children aged 12-15 years, which consist of 41 boys and 81 girls. Sampling technique was using total sampling technique. Results: This research found that the DMF-T index of 12-15 years old children in 2nd Junior High School (SMP Negeri 2) PTPN VIII Pangalengan is 4,39. Conclusion: DMF-T index of 12-15 years old children in 2nd Junior High School (SMP Negeri 2) PTPN VIII Pangalengan falls into medium.